Ethnobotany of medicinal plants in the dayak limbai tribe - Markus Iyus Supiandi; Yakobus Bustami; Benediktus Ege; Hendrikus Julung; Florentina Rahayu Esti Wahyuni; Jul Afrianus (STKIP Persada Khatulistiwa Sintang, 2021)
The use of medicinal plants by the Dayak Limbai tribe has been going on for a long time, it's just that knowledge related to the use of plants as medicinal ingredients has not been well documented. The aims of this study are 1) to identify plant species that have the potential as medicinal ingredients; 2) describe the part of the medicinal plant used; 3) describe how to use plants as medicine by the Dayak Limbai people. This research was conducted with a qualitative descriptive approach. The data collected consisted of the diversity of medicinal plants (local names of medicinal plants, scientific names of medicinal plants, medicinal plant families, parts used, and their utilization). Data collection using structured interview sheets. Data analysis using content analysis. The results obtained as many as 82 types of plants used to treat 64 types of diseases. The most widely used plant species by the Dayak Limbai people are from the Zingiberaceae family.